Patent pledges : global perspectives on patent law's private ordering frontier - Contreras, Jorge L., 1966-; Jacob, Meredith (Edward Elgar Publishing, 2017)
Patent holders are increasingly making voluntary, public commitments to limit the enforcement and other exploitation of their patents. The best-known form of patent pledge is the so-called FRAND commitment, in which a patent holder commits to license patents to manufacturers of standardized products on terms that are "fair, reasonable and non-discriminatory." Patent pledges have also been appearing in fields well beyond technical standard-setting, including open source software, green technology and the biosciences. This book explores the motivations, legal characteristics and policy goals of these increasingly popular private ordering tools. Jorge Contreras and Meredith Jacob bring together work by more than a dozen international experts who examine the phenomenon of patent pledges from a variety of perspectives and analytical frameworks. The book assesses patent pledges as mechanisms for facilitating platform promotion, open innovation, economic development and environmental sustainability. Legal practitioners who are involved in intellectual property licensing, litigation and business transactions will find this book a key resource, as will in-house lawyers and managers at firms engaged in technology development and standardization. It will also be a key reference for scholars in law, economics, business and political science.